Prognosis and Immune Infiltration of Chromobox Family Genes in Sarcoma - Zhou, Jian; Chen, Ziyuan; Zou, Ming; Wan, Rongjun; Wu, Tong; Luo, Yingquan; Wu, Gen; Wang, Wanchun; Liu, Tang (Frontiers in Oncology, 2021)
Background Chromobox family genes (CBXs) are known to play roles in numerous modifications of the chromatin in order to inhibit the transcription of target genes. CBXs have been shown to be expressed at high levels in many types of cancer and can also serve as a target gene for therapeutic purposes. However, little is known about the expression and prognostic value of CBXs in human sarcomas. Methods The transcription level of CBXs was analyzed using the Oncomine dataset, and the differential expression of CBXs in sarcoma was reported by the Gene Expression Profiling Interactive Analysis (GEPIA) dataset. We also used the CCLE dataset to evaluate the expression of CBXs in a sarcoma cell line. The prognostic value of CBXs was analyzed using GEPIA and Kaplan–Meier analysis. In addition, the corrections between CBXs and their co-expressed genes were reported using Oncomine and GEPIA datasets. DAVID was used to perform GO function enrichment analysis for the CBXs and their co-expression genes. Finally, TIMER was used to analyze the immune cell infiltration of CBXs in patients with sarcoma. Results HP1-α/β/γ (CBX1/3/5) and CBX4/6/8 were found to be overexpressed in human sarcoma, and CBXs were upregulated in almost all the sarcoma cell line. The expression levels of HP1-α/β/γ (CBX1/3/5) and CBX7 were associated with overall survival (OS) in patients with sarcoma, while high expression levels of CBX7 were related to disease-free survival (DFS). In addition, the expression levels of CBX2/6/7 were related to recurrence-free survival (RFS). We also found that the CBX family was positively correlated with the infiltration of immune cells, including CD8+ T cells, CD4+ T cells, B cells, macrophages, neutrophils, and dendritic cells, in sarcoma. Conclusions The results from the present study indicated that CBXs were significantly associated with prognosis and immunological status in sarcoma. These data suggest that CBXs could serve as potential biomarkers for prognosis and immune infiltration in human sarcoma.